MODIFIKASI ALAT TANAM TIPE DORONG UNTUK MEMAKSIMALKAN PEMBUDIDAYAAN WORTEL (Daucus carrota) - Mu'minin, Muhammad Amirul; Caronge, Muhammad Wiharto; Kadirman, Kadirman (Universitas Negeri Makassar, 2018)
This study aims to design the tool and know the tool's performance that is total average number of seeds that falling with planting tools designed. The research's data of result of were obtained from testing of the tool's performance on three seedbed with one time test on every seedbed. The first seedbed on right lane is 2.4 seeds/falling point and left lane is 2.3 seeds/falling point. The second seedbed on right lane is 2.2 seeds / falling point and left lane is 2.3 seed / falling point. The third seedbed on right lane is 2.2 seeds / falling point and left lane is 2.3 seeds / falling point. While for planting spacing first seedbed on right lane is 5.14 cm / falling point and left lane is 5.10 cm / falling point, second seedbed on right lane is 5.14 cm / falling point and left lane is 5.11 cm / fall point, third seedbed on right lane is 5.14 cm / fall point and left lane is 5.11 cm / fall point.